(untitled) (Bangladesh Journal of Medical Science, 2025)
Background Advanced technology in digital dentistry have transformed oral healthcare prevention and diagnosis. This study examines how digital dentistry impacts precision diagnostics, patientcentric preventative care, and treatment planning efficiency. Intraoral scanners, digital radiography, CAD/CAM technology, and artificial intelligence have transformed oral healthcare, promising more precision, efficiency, and patient-centered care. Methods An extensive search was conducted in electronic databases such as PubMed, Scopus, Google Scholar, and Web of Science to locate relevant studies published between January 2013 and 2023. Research on the diagnostic and preventative uses of digital dentistry was included. Findings Intraoral scanners and digital radiography enable precise oral structural visualization and assessment. This improved precision aids early detection and targeted therapies. Digital tools enable patient-centric preventative treatment that is adapted to individual needs. Treatment planning is faster and more predictable with CAD/CAM and collaborative communication tools. Artificial intelligence improves diagnostics by giving fast, accurate results and supporting evidence-based decision-making. Conclusion The talk emphasizes digital dentistry’s positive impact on oral health. From precision diagnostics to patient-centered preventative care and efficient treatment planning, digital dentistry has big impacts. AI is transforming oral healthcare, solidifying its role in the future. As digital dentistry evolves the synergistic combination of these technology breakthroughs offers more precise, efficient, personalized, and patient-centered oral healthcare. Digital dentistry will shape oral healthcare in the future. BJMS, Volume: 24. Supplementary Issue 2025, Page : 160-169